Incremental cost–effectiveness of percutaneous versus surgical closure of atrial septal defects in children under a public health system perspective in Brazil. (November 2014) - Costa, Rodrigo; Pedra, Carlos AC; Ribeiro, Marcelo; Pedra, Simone; Ferreira-Da-Silva, André Luis; Polanczyk, Carisi; Berwanger, Otávio; Biasi, Alexandre; Ribeiro, Rodrigo
<x xml:space="preserve">Abstract</x> Introduction: Cost–effectiveness (CE) studies of percutaneous (PC) versus surgical (SC) atrial septal defect closure are lacking. Methods: A systematic literature review in children and a CE analysis based on a model of long-term outcomes were performed. Direct costs of PC and SC were US$8700 (defined arbitrarily) and US$5700 (actually paid), respectively. Three-times the Brazilian GDI (US$28, 700) per year of life saved (with a discount rate of 5%) was used as a limit for willingness-to-pay. Discussion: PC had a high (US$104, 500) incremental CE ratio despite lower complication rates, shorter hospital stay and better (nonsignificant) adjusted life expectancy. PC would be cost–effective if it cost US$6400 or SC had an 8% loss of utility or its indirect costs were US$2250. Costs of PC should be reduced to be cost–effective in the Brazilian public health system. Indirect costs and impact on quality of life should be further assessed.